Quercetin attenuates the proliferation, inflammation, and oxidative stress of high glucose-induced human mesangial cells by regulating the miR-485-5p/YAP1 pathway. (7th February 2022) - Wan, Huan; Wang, Yaping; Pan, Qingyun; Chen, Xia; Chen, Sijun; Li, Xiaohui; Yao, Weiguo
Background: Diabetic nephropathy (DN) is a kidney damage caused by diabetes and the main cause of end-stage renal disease. However, the current treatment of DN has many limitations. Quercetin is a bioflavonoid compound with therapeutic benefits in metabolic diseases. This study aims to determine the therapeutic potentials and underlying mechanism of quercetin on DN. Methods: We collected blood samples from DN patients and healthy controls and treated human mesangial cells (HMCs) with high glucose (HG) to establish an in vitro model of DN. Then we assessed the expression difference of miR-485-5p as well as YAP1 in serum of DN patients and healthy controls and between HG-induced HMCs and control cells. qRT-PCR and western blot were performed to assess miR-485-5p and YAP1 expression levels; CCK-8 and ELISAs were used to examine cell proliferation, inflammation, and oxidative stress. Dual luciferase reporter assay was implemented to detect the binding of miR-485-5p and YAP1 mRNA sequence. Results: Quercetin suppressed proliferation, inflammation, and oxidative stress of HMCs induced by HG. As for mechanism, miR-485-5p directly bound to YAP1 and inhibited YAP1 expression. The downregulation of miR-485-5p and upregulation of YAP1 were also observed in the serum of DN patients. Quercetin modulated miR-485-5p/YAP1 axis to regulate HG-induced inflammation and oxidative stress. Conclusion: Quercetin inhibits the proliferation, inflammation, and oxidative stress of HMCs induced by HG through miR-485-5p/YAP1 axis, which might provide a novel treatment strategy for DN.